Telling Sauna Stories - Erin Alexiuk (Journal of Awareness-Based Systems Change, 2022)
Autoethnography is a qualitative research methodology that centers self in social and cultural analysis. Building on the emerging study of inner work in systems transformations, this article explores the potential contributions of autoethnography as a methodological companion to systems analysis. By layering excerpts from an autoethnography exploring my maternal family’s history as Finnish immigrants to northern Ontario, Canada with conventional academic prose, I model what this approach might look like and discuss its relationship with established systems approaches. In writing this piece, my intentions are exploratory: what can we learn from those who study and practice systems change if they turned their gaze inward and revealed their journey for others to learn from? Using an autoethnographic approach, I surfaced nuanced understandings of highly complex social and cultural processes. In particular, a previously unexamined connection to ancestry and cultural identity emerged through sauna stories told by female relatives and my own introspection into a life-long relationship with sauna bathing. The partial, dynamic narratives resulting from this work better match our incomplete understandings of complex systems and can even transform the lives of those engaged in systems change.